Extreme Climate Anomalies Enhancing Cyanobacterial Blooms in Eutrophic Lake Taihu, China. Issue 7 (21st July 2021) - Qin, Boqiang; Deng, Jianming; Shi, Kun; Wang, Jia; Brookes, Justin; Zhou, Jian; Zhang, Yunlin; Zhu, Guangwei; Paerl, Hans W.; Wu, Li
Abstract: Climate warming in combination with nutrient enrichment can greatly promote phytoplankton proliferation and blooms in eutrophic waters. Lake Taihu, China, is a large, shallow and eutrophic system. Since 2007, this lake has experienced extensive nutrient input reductions aimed at controlling cyanobacterial blooms. However, intense cyanobacterial blooms have persisted through 2017 with a record‐setting bloom occurring in May 2017. Causal analysis suggested that this bloom was sygenerically driven by high external loading from flooding in 2016 in the Taihu catchment and a notable warmer winter during 2016/2017. High precipitation during 2016 was associated with a strong 2015/2016 El Niño in combination with the joint effects of Atlantic Multi‐decadal Oscillation (AMO) and Pacific Decadal Oscillation (PDO), while persistent warmth during 2016/2017 was strongly related to warm phases of AMO and PDO. The 2017 blooms elevated water column pH and led to dissolved oxygen depletion near the sediment, both of which mobilized phosphorus from the sediment to overlying water, further promoting cyanobacterial blooms. Our finding indicates that regional climate anomalies exacerbated eutrophication via a positive feedback mechanism, by intensifying internal nutrient cycling and aggravating cyanobacterial blooms. In light of global expansion of eutrophication and blooms, especially in large, shallow and eutrophic lakes, these regional effects of climate anomalies are nested within larger scale global warming predicted to continue in the foreseeable future. Plain Language Summary: Climate warming in combination with eutrophication can greatly promote algal blooms (algal scum aggregate at water surface) in eutrophic waters. But we know little of resultant response of algal bloom occurrence. Utilizing Lake Taihu, China, we examined how a large, shallow eutrophic system responds to extreme climate anomalies such as winter warmth and heavy rainfall. Intense algal blooms have persisted through 2017, after a decadal intensive effluent control. Causal analysis suggested that this bloom was synergistically driven by high external loading from flooding in 2016 and a notable warmer winter during 2016/2017, which were associated with a strong 2015/2016 El Niño, and joint effects of Atlantic Multi‐decadal Oscillation (AMO) and Pacific Decadal Oscillation (PDO), whilst persistent warmth during 2016/2017 was strongly related to warm phases of AMO and PDO. Intense blooms led to water column pH increase and dissolved oxygen depletion near the bottom, both of which mobilized phosphorus from the sediment to overlying water and promoting algal blooms. Our finding indicates that regional climate anomalies exacerbated eutrophication via a positive feedback mechanism, by intensifying internal nutrient cycling and aggravating algal blooms. Key Points: High rainfall in 2016 and warm winter in 2016/2017 in Lake Taihu was caused by a strong 2015/2016 El Niño and Atlantic Multi‐decadal Oscillation and Pacific Decadal Oscillation Warm winter in combination with high precipitation greatly promote phytoplankton proliferation and intense blooms in 2017 in Lake Taihu Intense blooms led to high pH and dissolved oxygen depletion and further mobilized phosphorus from the sediment to promote blooms